PENGARUH VARIASI KONSENTRASI ASAM ASETAT PADA BIOKONVERSI KEPING BIJI KAKAO (Theobroma cacao L.) TERHADAP SIFAT KIMIA DAN SENSORIS PASTA KAKAO - , Fahmi Fauzi Dzulqarnain; , Prof. Dr.Ir. Haryadi, M.App.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fermentation process is one of the important step on producing wellflavored cocoa beans. The alternative fermentation-like method of cocoa beans was the bioconversion process, controlled soaking of the cocoa nibs in an one aqueous acidic medium that was to decrease the pH of the cocoa nibs, and the temperature was controlled. The purposes of this research was to produce high precursor flavor compund similiar to fermented cocoa beans by chemical and sensory quality. The research was done in 4 steps i,e. : pre-treated sample of cocoa beans (depulping and deshelling), bioconversion process, drying of cocoa nibs, and roasting of cocoa liquor. The soaked of cocoa nibs was done in three steps of acetic acid buffer solution at pH 2,7